Biological removal of deltamethrin in contaminated water, soils and vegetables by Stenotrophomonas maltophilia XQ08. (September 2021) - Wu, Xiaomao; Zhang, Cheng; An, Huaming; Li, Ming; Pan, Xinglu; Dong, Fengshou; Zheng, Yongquan
Abstract: The consideration of ecological and human health risk is an emerging concern with the excessive or inappropriate use of deltamethrin. In this study, the degradation conditions of the newly deltamethrin-degrading strain Stenotrophomonas maltophilia XQ08 were optimized, which were temperature 35 °C, pH 7.5, cell concentration 5.5 × 10 8  cfu/mL, and substrate concentration 50 mg/L. Strain XQ08 could effectively degrade deltamethrin into three smaller molecular weight and lower toxic compounds. Enriched strain XQ08 was immobilized in a charcoal-alginate matrix and possessed more prominent biodegradability, reusability, storability and thermostability than free XQ08. In a continuous reactor system, immobilized XQ08 could averagely remove 78.81% of deltamethrin at the gradient influent dosages of 50, 75 and 100 mg/L within 30 d. Immobilized XQ08 introduced into the filed brown and yellow soils exhibited a superior degradation potential for deltamethrin with the half-lives of 1.77 and 2.04 d, which were 2.39 and 2.14 folds, or 6.09 and 5.47 folds faster than free XQ08 degradation (4.23 and 4.37 d) or natural dissipation (10.78 and 11.16 d), respectively. Moreover, application of free XQ08 decreased the persistence of deltamethrin in Brassica pekinensis and Brassica chinensis from 5.47 and 6.23 to 2.05 and 2.32 d, or by 62.52% and 62.76%, respectively. This study provides a feasible, effective and rapid biological removal technology for deltamethrin-contaminated environments in situ. Graphical abstract: Image 1 Highlights: The degradation condition of deltamethrin by Stenotrophomonas maltophilia XQ08 was optimized. Strain XQ08 could efficiently degraded deltamethrin into three lower toxic compounds. Immobilized XQ08 possessed superior biodegradability, reusability, storability and thermostability. Free or immobilized XQ08 rapidly removed deltamethrin in water, soils and vegetables.